2021
DOI: 10.1002/ppp3.10224
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of sorghum grain yield and nutrition: A role for arbuscular mycorrhizal fungi regardless of soil phosphorus availability

Abstract: Societal Impact StatementSorghum is an important cereal crop that provides calories and nutrients for much of the world's population, and it is often grown with low fertiliser input. Optimising the yield, nutritive content and bioavailability of sorghum grain with minimal input is of importance for human nutrition, and arbuscular mycorrhizal (AM) fungi have previously shown potential to assist in this. Across sorghum genetic diversity, AM fungi improved the yield, nutrition and zinc and iron bioavailability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 63 publications
0
10
0
1
Order By: Relevance
“…These treatments resulted in plant available (Colwell) P concentrations of 5.11 mg kg −1 (±1.1), 16 mg P kg −1 (±0.92) and 29 mg P kg −1 (±3.2), in the low, medium and high P treatments respectively. Thus the low P treatment was below the critical P values for sorghum (15–22 mg P kg −1 ), while the medium P treatment fell within these values and the high P treatment resulted in P availability that was above these values (Peverill et al, 1999; Watts‐Williams et al, 2021). All plants were grown in the glasshouse, watered ad libitum with tap water for 12 weeks with 11 h day length and day/night temperatures of 28°C/18°C, while average daylight in the glasshouse for this period was 750 μmol m −2 s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…These treatments resulted in plant available (Colwell) P concentrations of 5.11 mg kg −1 (±1.1), 16 mg P kg −1 (±0.92) and 29 mg P kg −1 (±3.2), in the low, medium and high P treatments respectively. Thus the low P treatment was below the critical P values for sorghum (15–22 mg P kg −1 ), while the medium P treatment fell within these values and the high P treatment resulted in P availability that was above these values (Peverill et al, 1999; Watts‐Williams et al, 2021). All plants were grown in the glasshouse, watered ad libitum with tap water for 12 weeks with 11 h day length and day/night temperatures of 28°C/18°C, while average daylight in the glasshouse for this period was 750 μmol m −2 s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study demonstrated that well-established AM symbiosis could substantially improve licorice growth and facilitate glycyrrhizin and liquiritin accumulation under P limitation ( Xie et al, 2018 ), mainly attributed to improved plant P nutrition by AM symbiosis ( Xie et al, 2019 ). In this study, we investigated mycorrhizal effects on plant growth under P deficiency at two growth stages, representing the less developed AM symbiosis but high plant P demand stage ( Li et al, 2006 ; Watts-Williams et al, 2022 ) and AM symbiosis well-established stage, respectively. We hypothesized that plants would suffer P deficiency even with AM symbiosis especially in the early growth stage, thus resulting in increase in internal P recycling by modulating C allocation and partitioning.…”
Section: Discussionmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungus availability affects wheat growth (Watts-Williams et al, 2022). These organisms work in harmony with plant roots to increase plant resilience to stress and nutrient availability (Zhang et al 2019).…”
Section: Introductionmentioning
confidence: 99%